The role of instability with plyometric training in sub-elite adolescent soccer players - Granacher, U.; Prieske, O.; Majewski, M.; Büsch, D.; Muehlbauer, T. (International Journal of Sports Medicine, 2015)
The purpose of this study was to investigate the effects of plyometric training on stable (SPT) vs. highly unstable surfaces (IPT) on athletic performance in adolescent soccer players. 24 male sub-elite soccer players (age: 15±1 years) were assigned to 2 groups performing plyometric training for 8 weeks (2 sessions/week, 90?min each). The SPT group conducted plyometrics on stable and the IPT group on unstable surfaces. Tests included jump performance (countermovement jump [CMJ] height, drop jump [DJ] height, DJ performance index), sprint time, agility and balance. Statistical analysis revealed significant main effects of time for CMJ height (p<0.01, f=1.44), DJ height (p<0.01, f=0.62), DJ performance index (p<0.05, f=0.60), 0-10-m sprint time (p<0.05, f=0.58), agility (p<0.01, f=1.15) and balance (p<0.05, 0.46=f=1.36). Additionally, a Training group×Time interaction was found for CMJ height (p<0.01, f=0.66) in favor of the SPT group. Following 8 weeks of training, similar improvements in speed, agility and balance were observed in the IPT and SPT groups. However, the performance of IPT appears to be less effective for increasing CMJ height compared to SPT. It is thus recommended that coaches use SPT if the goal is to improve jump performance.